Gabapentin for the Treatment of Vulvodynia: A Randomized Controlled Trial. Issue 9 (September 2018) - Brown, Candace S.; Bachmann, Gloria A.; Wan, Jim; Foster, David C.
Abstract : (Abstracted from Obstet Gynecol 2018;131:1000–1007) Vulvodynia is a chronic pain syndrome with a lifetime prevalence of 7% to 16%. Only a small number of randomized clinical trials (RCTs) have been conducted on vulvodynia.